Geoquímica das rochas granitóides da região de Gouveia, centro de Portugal - Neiva, A.M.R. (2003)
Several types of peraluminous Hercynian granites containing generally more primary muscovite than Fe2+-biotite + chlorite, have mainly A/CNK values greater than 1.15, but ranging between 1.01 and 1.41 and δ18O values of 10.34-13.52% and are interpreted of S-type. A Mg-biotite granidorite of I-type having A/CNK of 0.99-1.10 and δ18O of 8.84% also occurs in the Gouveia area. Variation diagrams of major and trace elements for the oldest four granites and granodiorite show five independent fractionation trends, suggesting that they correspond to five distinct granitic magmas. The granites are probably originated by partial fusion of heterogeneous metasedimentary materials, while granodiorite may result from partial of igneous material or has a mantelic origin.